Real estate advertising in today’s auction industry - Regehr, Douglas K. (Kansas State University, 2011)
Purple Wave, Inc. has five major auction categories: Real Estate; Business Liquidation; Heavy Equipment (Agricultural and Construction); State Surplus; and Personal Property). Although Purple Wave is rapidly expanding in all categories its current focus is on increasing its real estate sales category. Selling real estate via the auction method is the fastest growing sector of the auction industry. The auction process provides a time-defined result, usually 60 to 90 days from contract signing to closing. The process also establishes a true market value established by the public. I have been tasked with evaluating our current real estate marketing methods. I am to determine the best way to allocate marketing funds to attract the most viable, competitive, well funded, and aggressive real estate bidders. The economic rationale of this issue is the ability to market real estate for higher sale prices. The cost of this issue cannot be measured in terms of a direct expense. The issue is how the company could best spend the marketing funds they receive to ensure the auction will reach the maximum price for the property. Purple Wave is paid on a percent of the sale price. The customer and company have everything to gain from a higher sale price since both will receive a larger profit. Purple Wave would like this issue to be solved with the development of a marketing menu. The real estate teams can use this new menu to show a potential customer how their marketing funds will be used to gain them the maximum amount of advertising exposure. The format can also show sellers how we plan to invest the marketing funds in specific promotional areas.
Keywords: Auction; Real estate; Advertising; Economics, Agricultural (0503)